2006
DOI: 10.1016/j.pain.2006.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of synchrony demonstrates ‘pain networks’ defined by rapidly switching, task-specific, functional connectivity between pain-related cortical structures

Abstract: Imaging studies indicate that experimental pain is processed in multiple cortical areas which are often characterized as a network. However, the functional connectivity within the network and the other properties of the network is poorly understood. Substantial evidence demonstrates that synchronous oscillations between two cortical areas may indicate functional connectivity between those areas. We test the hypothesis that cortical areas with pain-related activity are functionally connected during attention to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
76
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 70 publications
12
76
1
Order By: Relevance
“…Indeed, changes of ␥-band neuronal oscillations clearly appear integral to a number of complex cognitive functions ranging from attention, language, memory and mental practice (Lutz et al, 2004; Bastiaansen and Hagoort, 2006) to crossmodal (Kanayama et al, 2009), and sensorimotor integration (Alonso et al, 1996;Wallace et al, 1996;Bauer et al, 2006;Szurhaj and Derambure, 2006). Relevant to the present study is that ␥-band activity plays a specific role in first-hand pain processing (Chen and Herrmann, 2001;Ohara et al, 2006;Gross et al, 2007;Hauck et al, 2007). In particular, a recent MEG study showed that pain-induced ␥-band oscillations in the primary somatosensory cortex were related to the subjective perception of pain stimulus intensity rather than to the objective intensity of the stimulus itself (Gross et al, 2007).…”
Section: Discussionsupporting
confidence: 51%
“…Indeed, changes of ␥-band neuronal oscillations clearly appear integral to a number of complex cognitive functions ranging from attention, language, memory and mental practice (Lutz et al, 2004; Bastiaansen and Hagoort, 2006) to crossmodal (Kanayama et al, 2009), and sensorimotor integration (Alonso et al, 1996;Wallace et al, 1996;Bauer et al, 2006;Szurhaj and Derambure, 2006). Relevant to the present study is that ␥-band activity plays a specific role in first-hand pain processing (Chen and Herrmann, 2001;Ohara et al, 2006;Gross et al, 2007;Hauck et al, 2007). In particular, a recent MEG study showed that pain-induced ␥-band oscillations in the primary somatosensory cortex were related to the subjective perception of pain stimulus intensity rather than to the objective intensity of the stimulus itself (Gross et al, 2007).…”
Section: Discussionsupporting
confidence: 51%
“…Notably, these findings could be extended to pain processing in a recent study conducted in neurosurgical awake patients by demonstrating attention to painful laser stimuli to enhance intracranially recorded synchrony between distinct cortical pain-related regions (Ohara et al, 2006). The pattern of synchrony changed between the primary somatosensory cortex, the medial frontal cortex, and the insula as the patient switched from a distracted state to attention to the stimuli by counting the total number.…”
Section: Discussionmentioning
confidence: 70%
“…Top-down influences such as focused attention may act by modulating subthreshold oscillations in sensory assemblies and by enhancing the gain of oscillatory responses to stimuli that match stored contex-tual information Herrmann et al, 2004). Along the same lines, ␥-band oscillations might also play an integral role in pain perception and processing (Chen and Herrmann, 2001;Croft et al, 2002;Ohara et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies showed nearly simultaneous pain-evoked activations in S1, S2 and ACC [Frot et al, 2008;Ohara et al, 2004;Ploner et al, 1999] which differ from more sequential activation patterns in other modalities and suggest a partly parallel organization of pain processing in the human brain. Other studies applied coherence analyses and showed pain-related changes in functional connectivity between brain areas related to pain [Llinas et al, 1999;Ohara et al, 2008;Ohara et al, 2006;Sarnthein and Jeanmonod, 2008]. However, temporal sequences and correlations do not directly imply information on causal relationships between neural activations.…”
Section: Introductionmentioning
confidence: 99%